2022
DOI: 10.30574/wjarr.2022.14.1.0346
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical study of TGF-β, PDL-1, and IL-10 in patients with Toxoplasma gondii

Abstract: The aim of this study to evaluate the expression of Programmed cell death-1 (PD-1), TGF- ß, and IL-10 in placental tissue of aborted women and the correlation with Toxoplasma.gondii (T. gondii) and the correlation of these cytokines with each other and with toxoplasmosis, during an abortion. The placental tissue samples have been processed and used for immunohistochemistry to study the expression of PDL-1, IL-10, and TGF-β. There was an increase in expression of TGF-β, PDL-1, and IL-10 in the placental tissue … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 62 publications
1
1
0
Order By: Relevance
“…The results of this study suggest that the degree of coronary heart disease (CHD) may be related to the betatrophin, ANGPTL4, LPL pathway. Furthermore, the results showed that LPL and ANGPTL3 levels increased in people with CHD diagnoses, and the rising trends observed for both of these markers were consistent with the findings reported in (16). The functional difference between members of the ANGPTL family is attributed to the variation between their C-terminal and N-terminal domains, as demonstrated by the results of previous studies.…”
Section: Discussionsupporting
confidence: 88%
“…The results of this study suggest that the degree of coronary heart disease (CHD) may be related to the betatrophin, ANGPTL4, LPL pathway. Furthermore, the results showed that LPL and ANGPTL3 levels increased in people with CHD diagnoses, and the rising trends observed for both of these markers were consistent with the findings reported in (16). The functional difference between members of the ANGPTL family is attributed to the variation between their C-terminal and N-terminal domains, as demonstrated by the results of previous studies.…”
Section: Discussionsupporting
confidence: 88%
“…These methods (in comparison to other analytical methods) are characterized by sensitivity and tuning, as well as selectivity ranging from good to medium, and are quick and low-cost, with the ability to analyse both organic and inorganic compounds (5). In the last decade, the importance of these approaches has risen dramatically in terms of the construction of equipment and methods for sample preparation (6). Spectroscopy methods are used in the pharmaceutical study of any medication to determine the drug's structure and how it interacts with the other ingredients in the preparation (7).…”
Section: Spectrophotometric Methods Of Analysismentioning
confidence: 99%